Intrinsic correlation between β-relaxation and spatial heterogeneity in a metallic glass - F. Zhu (Nature Portfolio, 2016)
Beta-relaxation in glasses is commonly attributed to the confined motions of constituent atoms in nanosized domains, but there is no direct evidence so far. Here, Zhu et al. show the correlation between the evolution of spatial heterogeneity at nanoscale and beta-relaxation below glass transition point.